A Study of One State's School District Physical Restraint and Seclusion Policies. (November 2021) - Van Acker, Eryn Y.; Kane, Elisabeth J.; Bricko, Nicole C.; Peterson, Reece L.
This descriptive analysis of policy content examined local school district policies on physical restraint and seclusion in one Midwestern state that did not have state legislation on these topics to determine whether districts had policies and, if so, whether their content included recommended principles from the U.S. Department of Education. No previous research has addressed district policies. A maximum variation sample of 90 districts was examined to determine whether policies were in place, whether recommended principles were included, and whether policies varied based on student enrollment. Although almost all districts had policies, many of the federally recommended principles were not addressed across the sample and less than 10% of the district policies indicated that these procedures should only be used in the case of imminent danger of serious injury to self or others. District enrollment size did not affect policy, but the substance of the policy was determined by the districts' policy source from advising attorneys.